Prevalence of thyroid dysfunction in postpartum women with suboptimal iodine and selenium and adequate iron status. (3rd June 2021) - Jin, Ying; Coad, Jane; Zhou, Shao J.; Skeaff, Sheila; Ramilan, Thiagarajah; Brough, Louise
Abstract: Objective: Postpartum women experience thyroid dysfunction at twice the prevalence of the general population. Adequate biosynthesis of thyroid hormones depends on three trace elements: iodine, selenium and iron. This study aimed to investigate thyroid dysfunction within a cohort of women at six months postpartum in relation to iodine, selenium and iron status. Design: This cross‐sectional study was part of an observational longitudinal cohort Mother and Infant Nutrition Investigation; data obtained at six months postpartum are reported. Subjects: Mother‐infant pairs (n = 87) were recruited at three months postpartum and followed up at six months postpartum (n = 78). Measurements: Thyroid hormones (free triiodothyronine, free thyroxine, thyroid‐stimulating hormone) and thyroid peroxidase antibodies were measured. Urinary iodine concentration, breast milk iodine concentration, serum thyroglobulin, plasma selenium, serum ferritin and serum soluble transferrin receptors were determined. Nonparametric data were expressed as median (25th, 75th percentile). Results: Thyroid dysfunction was found in 18% of women, and 4% of women had iron deficiency. Median urinary iodine concentration was 85 (43, 134) µg/L, median breast milk iodine concentration was 59 (39, 109) µg/L, and median serum thyroglobulin at 11.4 (8.6, 18.6) µg/L, indicating iodine deficiency. Median plasma selenium concentration was 105.8 (95.6, 115.3) µg/L. Women with marginally lower plasma selenium concentration were 1.12% times more likely to have abnormal TSH concentrations ( p  = .001). Conclusions: There was a high prevalence of thyroid dysfunction. Plasma selenium concentration was the only significant predictor of the likelihood that women had thyroid dysfunction within this cohort, who were iodine deficient and mostly had adequate iron status. Strategies are required to improve both iodine and selenium status to better support maternal thyroid function.